Experience in the treatment of chronic endometritis - N. I. Tapilskaya; Alevtina M. Savicheva; Kira V. Shalepo; Anastasiya A. Kopylova (IP Berlin A.V., 2020)
At present, bacterial biofilms play a significant role in chronic endometritis. In our clinical case, a patient with a history of infertility has had no sex life for several years, but bacterial vaginosis recurs monthly. Ascending bacterial infection with chronic endometritis was confirmed by immunohistochemistry data (detection of CD138), as well as microbiological data (detection of anaerobic microorganisms, including Gardnerella vaginalis and Atopobium vagine, in the endometrium). To treat chronic endometritis, we used antibiotic moxifloxacin, followed by administration of bovhyaluronidase azoximer (Longidaza) in the form of rectal suppositories. As a result of complex therapy, the patients endometrium improved (CD138 and anaerobic bacteria revealed), subsequent repeated insemination with donor sperm led to the onset of progressive pregnancy.